Cover Picture: Conjugation to Albumin‐Binding Molecule Tags as a Strategy to Improve Both Efficacy and Pharmacokinetic Properties of the Complement Inhibitor Compstatin (ChemMedChem 10/2014). Issue 10 (October 2014) - Huang, Yijun; Reis, Edimara S.; Knerr, Patrick J.; van der Donk, Wilfred A.; Ricklin, Daniel; Lambris, John D.
<x xml:space="preserve">Abstract</x> The front cover picture shows the chimeric peptide ABM2‐Cp20, a derivative of the complement inhibitor compstatin, simultaneously binding to albumin (pink) and complement C3 (teal). Compstatin has shown promise in the treatment of immuno‐inflammatory disorders; however, optimization of its pharmacokinetic properties would extend long‐term systemic applications. The addition of a small albumin‐binding molecule tag to the compstatin peptide improves plasma protein binding yet also largely enhances target affinity, thereby preventing convertase (teal/green)‐mediated C3 activation, opsonization and cell damage (flash arrow) more efficiently. For more details, see the Communication by Daniel Ricklin, John D. Lambris et al. on p. 2223 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>